A Fluorescence‐based assay for screening β‐lactams targeting the Mycobacterium tuberculosis transpeptidase LdtMt2 - De Munnik, M; Lohans, C; Langley, G; Bon, C; Brem, J; Schofield, C (Wiley, 2019)
Mycobacterium tuberculosis L,D‐transpeptidases (Ldts), which are involved in cell wall biosynthesis, have emerged as promising targets for the treatment of tuberculosis. However, an efficient method for testing inhibition of these enzymes is not currently available. We present a fluorescence‐based assay for LdtMt2, which is suitable for high‐throughput screening. Two fluorogenic probes were identified that release a fluorophore upon reaction with LdtMt2, making it possible to assess the availability of the catalytic site in the presence of inhibitors. The assay was applied to a panel of β‐lactam antibiotics and related inhibitors; the results validate observations that the (carba)penem subclass of β‐lactams are more potent Ldt inhibitors than other β‐lactam classes, though unexpected variations in potency were observed. The method will enable systematic structure‐activity relationship studies on Ldts, facilitating the identification of new antibiotics active against M. tuberculosis.